Characterisation of C-C Ligand 7 (CCL7) as Asthma Genetic Marker in Pigtailed Monkey - Sela S Mariya,; Uus Saepuloh,; Novi Febriani,; Dyah Perwitasari-Farajallah,; Diah Iskandriati,; Huda S Darusman,; Joko Pamungkas, (Tropical Life Sciences Research, 2024)
The pigtailed monkey (Macaca nemestrina) is one of the species that have potency like the cynomolgus monkey that is widely used as an animal model for asthma study. The CCL7 gene has potential as a genetic marker because of the secreted chemokine that plays a role in asthma. The aims of this research are to characterise the CCL7 gene of pigtailed monkey, compare the structure of their CCL7 gene with other primate species and determine model 3D structure protein prediction of CCL7 protein. The amplicons were sequenced, and the results were analysed by the bioinformatics technique. The 3D CCL7 protein structure was predicted using I-TASSER. We have isolated 2221 bp sequences CCL7 gene and 109 amino acids from pigtailed monkey. Variation of CCL7 gene sequence between pigtailed monkey and other primate species (Macaca fascicularis, M. mulatta and Homo sapiens) was found in exon 1, exon 2 and exon 3 as CDS (Coding DNA Sequence) region. The analysis homology of nucleotides and amino acid sequences of the CCL7 gene indicated that the pigtailed monkey and three other primate species have a high homology rate with an identity score above 90%. Meanwhile, a comparative analysis of CDS and amino acid regions showed that the pigtailed monkey also has the highest similarity with the three other primate species with more than 90% identity score. The 3D structure protein prediction model of the CCL7 pigtailed monkey revealed the highest similarity with H. sapiens with an identity value of about 95%. Therefore, the pigtailed monkey CCL7 gene has high similarity with H. sapiens, which means that based on molecular similarity, the pigtailed monkey has the potential to be an animal model for asthma study, especially the study of molecular and the role of CCL7 in asthma pathogenesis.